Representation and content in student's exam note sheets - Ignatius Edi Santosa (Universitas PGRI Kanjuruhan Malang, 2022)
Various forms of representation are used to understand physics concepts. This study aims to reveal the representations used by students in summarizing their physics teaching materials. The observed representations include mathematical equations, verbal statements and graphs. The participants were students who attended lectures in two academic years, namely 2016 and 2018. Students were permitted to freely write a summary of lecture material that would be used as resources during the exam. The research investigated the types of representations used and their percentages. In addition, the content in the summary was also taken into consideration. The results showed that the representation of mathematical equations or formulas, verbal explanations and graphs were used by 100%, 97% and 40% of the total students, respectively. This finding is also reflected in the percentage of paper area used in the summary; the uses of formulas are 60%, verbal explanations are 32.5% and the remaining 4.2% are graphs. Most note sheets contain almost all of teaching material. This students’ tendency should be considered for teaching strategy.